Asymptotic Approximations to the Isothermal Pyrolysis of Deodara Leaves using Gamma Distribution - Dhaundiyal, Alok; Szent Istvan University, Mechanical Engineering PhD School, Faculty of Mechanical Engineering, Godollo, Hungary. (2017)
The main aim of th is paper pivote d ar ound th e influence of some parameters relev ant to biomass pyrolys is on the numerical solutions of the nth order distributed activation energy model (DAEM) using the Gamma distribution. The upper limit of ‘dE’ integral, frequency factor, reaction order, and the shape and rate parameters of the Gamma distribution are investigated. Analys is of the mathematical model is done with the help of asymptotic expansion.